2020
DOI: 10.1111/nyas.14350
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course of gastroesophageal reflux disease and impact of treatment in symptomatic young patients

Abstract: In symptomatic young patients with gastroesophageal reflux symptoms, early identification of progressive gastroesophageal reflux disease (GERD) is critical to prevent long‐term complications associated with hiatal hernia, increased esophageal acid and nonacid exposure, release of proinflammatory cytokines, and development of intestinal metaplasia, endoscopically visible Barrett's esophagus, and dysplasia leading to esophageal adenocarcinoma. Progression of GERD may occur in asymptomatic patients and in those u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 118 publications
0
7
0
Order By: Relevance
“…This is consistent with the study by Ayazi et al 22 who found that male sex was also an independent predictive factor. The fact that MSA is more effective in younger and male patients is of particular interest because this operation may have a profound impact on the course of GERD if performed in an earlier disease stage 23 . In addition, a recent population-based study showed lower recurrence rates after fundoplication in young men who would otherwise require several decades of PPI therapy 24 .…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the study by Ayazi et al 22 who found that male sex was also an independent predictive factor. The fact that MSA is more effective in younger and male patients is of particular interest because this operation may have a profound impact on the course of GERD if performed in an earlier disease stage 23 . In addition, a recent population-based study showed lower recurrence rates after fundoplication in young men who would otherwise require several decades of PPI therapy 24 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the higher rate of crural repair associated with MSA implantation in patients with severe GERD may explain the significantly higher rate of post-operative dysphagia observed in these individuals. In fact, crural repair has an additive effect on LES augmentation, and the combination of hiatoplasty and MSA may increase the incidence of post-operative dysphagia ( 26 , 27 ). Last but not least, there were no significant differences between the two patient groups regarding the post-operative rates of recurrent hiatal hernia, endoscopic dilation, and laparoscopic device removal.…”
Section: Discussionmentioning
confidence: 99%
“…Although there was a trend toward an abnormally higher post-operative score in the severe GERD group, the majority of these patients reached pH normalization. Despite the fact that even patients with severe GERD may benefit from MSA, we hypothesize that an earlier surgical intervention has the potential to prevent anatomical deterioration of the esophago-gastric barrier and Barrett's mucosal changes ( 26 ). In two recent studies, age younger than 40-45 years, male sex, GERD-HRQL total score >15, and abnormal DeMeester score were independent predictors of favorable outcome after MSA ( 5 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…A decline in the use of surgical fundoplication has been noted in the US over the past decade [18][19][20]. Further, early recognition and treatment of GERD in young patients is critical to prevent long-term complications, even in patients under continuous acid-suppressive medication [21]. Paradoxically, underuse of antireflux procedures is in contrast to the increasing recognition of GERD as a progressive disease leading to carditis, cardiac metaplasia, intestinal metaplasia, and eventually adenocarcinoma of the distal esophagus [22,23].…”
Section: Introductionmentioning
confidence: 99%